Quality of Life in Heterogeneous Anxiety Disorders: Changes Across Cognitive-Behavioral Treatments. Issue 3 (May 2020) - Wilner, Julianne G.; Dufour, Steven; Kennedy, Katherine; Sauer-Zavala, Shannon; Boettcher, Hannah; Farchione, Todd J.; Barlow, David H.
Quality of life is lower among individuals with anxiety disorders; however, this construct is rarely a focus in treatment research. This study explores changes in quality of life in a randomized, controlled trial of several cognitive-behavioral treatments (CBTs) for anxiety disorders. Adults with heterogeneous anxiety disorders ( N = 223) were randomly assigned to (a) unified protocol for transdiagnostic treatment of emotional disorders, (c) a single-disorder protocol targeting their principal diagnosis, or (c) a waitlist control condition, and assessed at baseline, posttreatment, and 6-month follow-up. At baseline, the sample evidenced deficits in quality of life, with no significant differences in quality of life across diagnoses or condition. Results suggest improved quality of life among participants in treatment, at similar rates across treatment condition and diagnostic category, and at levels significantly higher than the waitlist. Improvements were maintained through 6-month follow-up. This study supports CBT as effective in promoting quality of life.